Mating compatibility among four pest members of the Bactrocera dorsalis fruit fly species complex (Diptera: Tephritidae) - Schutze, M. K. (2013)
Bactrocera dorsalis (Hendel), Bactrocera papayae Drew & Hancock, Bactrocera philippinensis Drew & Hancock, and Bactrocera carambolae Drew & Hancock are pest members within the B. dorsalis species complex of tropical fruit flies. The species status of these taxa is unclear and this confounds quarantine, pest management, and general research. Mating studies carried out under uniform experimental conditions are required as part of resolving their species limits. These four taxa were collected from the wild and established as laboratory cultures for which we subsequently determined levels of prezygotic compatibility, assessed by field cage mating trials for all pair-wise combinations. We demonstrate random mating among all pair-wise combinations involving B. dorsalis, B. papayae, and B. philippinensis. B. carambolae was relatively incompatible with each of these species as evidenced by nonrandom mating for all crosses. Reasons for incompatibility involving B. carambolae remain unclear; however, we observed differences in the location of couples in the field cage for some comparisons. Alongside other factors such as pheromone composition or other courtship signals, this may lead to reduced interspecific mating compatibility with B. carambolae. These data add to evidence that B. dorsalis, B. papayae, and B. philippinensis represent the same biological species, while B. carambolae remains sufficiently different to maintain its current taxonomic identity. This poses significant implications for this group's systematics, impacting on pest management, and international trade.